2005
DOI: 10.1089/lap.2005.15.308
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Nephroureterectomy for Tuberculous Nonfunctioning Kidneys Compared with Laparoscopic Nephroureterectomy for Other Diseases

Abstract: The results of this study indicate that LNU for a tuberculous nonfunctioning kidney is a safe, effective, and less invasive treatment modality. Comparing our results with those of nephroureterectomy for other, benign diseases shows that the procedure has similar safety and efficacy even for tuberculous kidneys. Tuberculosis should not be considered a contraindication for a laparoscopic approach. Laparoscopic nephroureterectomy should be offered as the treatment modality of choice to all patients with tuberculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In our cases, we performed all surgeries by retroperitoneal laparoscopic approach for we have high volume of experience with this approach ( 12 ). Current researches have demonstrated that the laparoscopic operation for inflammatory nonfunctioning kidney can be accomplished through either the transperitoneal or the retroperitoneal approaches ( 5 , 7 ), and the choice depends mainly on the surgeon’s educational background and laparoscopic experiences. Although the retroperitoneal approach has some disadvantages such as the limited working space, difficulty to identify the anatomical structure as well as a longer learning curve compared to the transperitoneal approach, it facilitates to control renal vessels early and avoids contamination with the pus and potential injury to intraperitoneal organs ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cases, we performed all surgeries by retroperitoneal laparoscopic approach for we have high volume of experience with this approach ( 12 ). Current researches have demonstrated that the laparoscopic operation for inflammatory nonfunctioning kidney can be accomplished through either the transperitoneal or the retroperitoneal approaches ( 5 , 7 ), and the choice depends mainly on the surgeon’s educational background and laparoscopic experiences. Although the retroperitoneal approach has some disadvantages such as the limited working space, difficulty to identify the anatomical structure as well as a longer learning curve compared to the transperitoneal approach, it facilitates to control renal vessels early and avoids contamination with the pus and potential injury to intraperitoneal organs ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few small series have been reported addressing laparoscopic nephroureterectomy for tuberculous nonfunctioning kidneys. The reported rates of successive laparoscopic surgery were between 77.8% and 100% ( 5 - 8 ). The largest cohort included only 31 patients ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In laparoscopic nephrectomy procedures for tuberculous nonfunctioning kidneys, the main reasons for conversion to open surgery are perinephric adhesions and intraoperative major hemorrhages. 9 Many investigators have regarded the tuberculous nonfunctioning kidney as a relative contraindication for laparoscopic nephrectomy because of the difficulty in dissection, high conversion rate, and the risk of spillage of caseous materials with subsequent dissemination of the disease. 10 In the present study, the most difficult part of the procedure was dissection of the dense adhesions and all the surgical steps.…”
Section: Discussionmentioning
confidence: 99%
“…1 Many of these problems requiring surgical intervention can now be managed by present-day laparoscopic techniques, providing the well-known benefits of minimally invasive surgery to the patient. These problems lead to difficulty in dissection because of poor anatomic landmarks.…”
Section: Discussionmentioning
confidence: 99%